Managing a monotown as a priority social and economic development area; AIP Conference Proceedings; Vol. 1800 : Youth, Science, Solutions: Ideas and Prospects (YSSIP-2016) - Trifonov V. A. Vladimir Aleksandrovich; Loyko O. T. Olga Timofeevna; Nesteruk D. N. Dmitry Nikolaevich; Zhironkin S. A. Sergey Aleksandrovich; Strekovtsova E. A. Ekaterina Aleksandrovna (2017, 2017)
Title screen